Ends of War : The Unfinished Fight of Lee's Army after Appomattox - Janney, Caroline E. (Book collections on Project MUSE., 2021)
"In this masterful work, Caroline E. Janney begins with a deceptively simple question: how did the Army of Northern Virginia disband? Janney slows down the pace of the events after Appomattox to reveal it less as a decisive end and more as the commencement of a chaotic interregnum marked by profound military and political uncertainty, legal and logistical confusion, and continued outbursts of violence. Janney blends analysis of large-scale political, legal, and military considerations with intimate narratives of individual soldiers considering their options and pursuing a wide range of decisions"--